2018
DOI: 10.1016/j.msea.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tempering temperature on microstructure, mechanical properties and bendability of direct-quenched low-alloy strip steel

Abstract: The tempering of re-austenized, quenched and tempered (RAQT) martensitic steels is an extensively studied and well understood field of metallurgy. However, a similar understanding of the effect of tempering on direct-quenched (DQ) high-strength steels has been lacking. Now, for the first time, the effect of tempering in the range of 250-650 °C on the strength, toughness, bendability, microstructure, crystallography and dislocation density of a DQ steel is reported. In the case of tempering at 570 °C, the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 26 publications
5
14
0
1
Order By: Relevance
“…The water quenched variant showed only minor traces of auto-tempering, but transition carbides began to form when tempering at 150 °C and 200 °C. The decrease of dislocation density with increasing tempering temperature followed the results found in the literature [22,25,[38][39][40]. Saastamoinen et al [38] reported dislocation density for both direct quenched (DQ) and reheated and quenched (RAQ) around 4.0 × 10 15 m −2 for martensite containing 0.1% C, which explains some of the difference with the current results.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The water quenched variant showed only minor traces of auto-tempering, but transition carbides began to form when tempering at 150 °C and 200 °C. The decrease of dislocation density with increasing tempering temperature followed the results found in the literature [22,25,[38][39][40]. Saastamoinen et al [38] reported dislocation density for both direct quenched (DQ) and reheated and quenched (RAQ) around 4.0 × 10 15 m −2 for martensite containing 0.1% C, which explains some of the difference with the current results.…”
Section: Discussionsupporting
confidence: 87%
“…The decrease of dislocation density with increasing tempering temperature followed the results found in the literature [22,25,[38][39][40]. Saastamoinen et al [38] reported dislocation density for both direct quenched (DQ) and reheated and quenched (RAQ) around 4.0 × 10 15 m −2 for martensite containing 0.1% C, which explains some of the difference with the current results. Using the same Williamson-Hall method as used here, in the case of 0.3% C martensite, Kennett et al [39] found dislocation densities in the as-quenched state in the range 8-10 × 10 15 m −2 , depending on PAGS, while Takebayashi et al [40] found a dislocation density of 2.0 × 10 16 m −2 .…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, tempering drives various phenomena such as the release of residual stress, decline in dislocation density and appearance of fine precipitates. These phenomena combine with the transformation of MA and decomposition of the secondary phase identified to control the mechanical properties of the steels [ 4 , 10 , 19 , 30 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…When dealing with bulk flanges of large dimensional size and complex structure, it should be taken into consideration that heat treatment would not be uniformly applied to each location of the products. However, most previous studies have tended to use standardized specimens [ 18 , 19 , 20 , 21 , 22 ] or sheet plates [ 9 , 16 ] of certain sizes to which uniform heat treatment can be applied within the specimens, so the results cannot be directly used to understand the bulk flanges. It is rather useful, especially from an industrial point of view, to investigate the effect of heat treatment on flanges by directly obtaining local properties of interest from the flanges under heat treatment processes.…”
Section: Introductionmentioning
confidence: 99%
“…On AHSS grade steel, the softening of the material is often seen as a limiting drawback for joining. However, tempering of martensite can also induce an increase in ductility [15][16][17]. Hence the local softening brought by LHT could grant an increase of ductility of martensitic steels where it's required.…”
Section: Introductionmentioning
confidence: 99%